Buprenorphine is a weak dopamine releaser relative to heroin, but its pretreatment attenuates heroin‐evoked dopamine release in rats - Dominic P. Isaacs; Ryan P. Leman; Thomas J. Everett; Hendrick Lopez‐Beltran; Lindsey R. Hamilton; Erik B. Oleson (Wiley, 2020)
Abstract Aims The United States of America is currently in an opioid epidemic. Heroin remains the most lethal opioid option with its death rate increasing by over 500% in the last decade. The rewarding and reinforcing effects of heroin are thought to be mediated by its ability to increase dopamine concentration in the nucleus accumbens shell. By activating Gi/o‐coupled μ‐opioid receptors, opioids are thought to indirectly excite midbrain dopamine neurons by removing an inhibitory GABAergic tone. The partial μ‐opioid receptor agonist buprenorphine is a substitution‐based therapy for heroin dependence that is thought to produce a steady‐state level of μ‐opioid receptor activation. But it remains unclear how buprenorphine alters dopamine release relative to heroin and how buprenorphine alters the dopamine‐releasing effects of heroin. Because buprenorphine is a partial agonist at the μ‐opioid receptor and heroin is a full agonist, we predicted that buprenorphine would function as a weak dopamine releaser relative to heroin, while functioning as a competitive antagonist if administered in advance of heroin. Methods We performed fast‐scan cyclic voltammetry in awake and behaving rats to measure how heroin, buprenorphine HCl, and their combination affect transient dopamine release events in the nucleus accumbens shell. We also performed a complimentary pharmacokinetic analysis comparing opioid plasma levels at time points correlated to our neurochemical findings. Results Both buprenorphine and heroin produced changes in the frequency of transient dopamine release events, although the effect of buprenorphine was weak and only observed at a low dose. In comparison with vehicle, the frequency of dopamine release events maximally increased by ~25% following buprenorphine treatment and by ~60% following heroin treatment. Distinct neuropharmacological effects were observed in the high‐dose range. The frequency of dopamine release events increased linearly with heroin dose but biphasically with buprenorphine dose. We also found that buprenorphine pretreatment occluded the dopamine‐releasing effects of heroin, but plasma levels of buprenorphine had returned to baseline at this time point. Conclusion These findings support the notion that low‐dose buprenorphine is a weak dopamine releaser relative to heroin and that buprenorphine pretreatment can block the dopamine‐releasing effects of heroin. The finding that high‐dose buprenorphine fails to increase dopamine release might explain its relatively low abuse potential among opioid‐dependent populations. Because high‐dose buprenorphine decreased dopamine release before occluding heroin‐evoked dopamine release, and buprenorphine was no longer detected in plasma, we conclude that the mechanisms through which buprenorphine blocks heroin‐evoked dopamine release involve multifaceted pharmacokinetic and pharmacodynamic interactions.